Innovations in neurosurgical education: the role of neurosurgical labs at neuroscience hospital of Baghdad in enhancing surgical skills - Moneer K. Faraj; Wamedh E. Matti; Rania H. Al-Taie (BMC Medical Education)
Abstract Background The field of neurosurgical education has seen significant advancements in recent years. However, the distribution of advanced neurosurgical education remains uneven, particularly in developing countries like Iraq. This study aims to evaluate the effectiveness of the neurosurgical lab at Neuroscience Hospital in Baghdad, focusing on its impact on surgical precision, skill and acquisition among neurosurgery residents. Method A cross-sectional survey targeted neurosurgeons, neurosurgical residents, and medical students actively utilizing the lab. The survey assessed the frequency of lab use, the impact of lab resources on clinical practice, and skill development. Data was analyzed using descriptive statistics and chi-square tests to explore associations between variables such as lab usage frequency, satisfaction, and professional development. Results Forty participants responded to the questionnaire. The results revealed that 60% of the participants expressed high satisfaction. The microscope and training models were considered highly impactful, with 80% of participants rating these resources as 4 or 5 on a 5-point scale. The chi-square tests revealed a statistically significant relationship between lab use frequency and satisfaction (χ² = 11.4, p = 0.010). Conclusion The neurosurgical lab at Neuroscience Hospital has proven to be an essential resource for enhancing surgical skills and promoting innovation. The findings highlight the need for continued integration of advanced technologies like 3D printing to improve neurosurgical training and outcomes in resource-limited settings.